Excavations at Samahij, Bahrain, and the implications for Christianity, Islamisation and settlement in Bahrain. (12th February 2021) - Insoll, Timothy; Carter, Robert; Almahari, Salman; MacLean, Rachel
Abstract: The episcopal seat of Meshmahig or Mašmahig is referred to in various historical sources, such as the synods of the Church of the East of 410 and 576. These sources have been extensively explored, and it is suggested that Mašmahig can be linked to the village of Samahij in north‐east Muharraq Island, Bahrain. However, archaeological evidence for a Christian presence in Samahij, or elsewhere in Bahrain, was lacking. Excavations completed within the village cemetery at Samahij uncovered part of a large building complex. Based on the architecture, associated material culture and chronology, it is suggested this building was occupied by a Christian community, perhaps as part of a monastery or even the episcopal palace itself. This was abandoned after Islamisation, seemingly in the eighth century. The results of the first season of excavations are described, and the implications for Christianity, Islamisation and settlement in Bahrain are considered.